Acolhimento de calouros na Universidade Tiradentes: um olhar no projeto mentoria - Graça, Janilce Santos Domingues (2021)
This article aims to understand the importance of the Mentoring Project in welcoming freshmen at Tiradentes University. The development of this research was based on the high dropout rates evidenced in the first year of undergraduate courses, in particular, the courses of Architecture, Law, Engineering (Environmental, Civil, Production, Mechatronics, Electrical and Oil), Nursing, Nutrition and Dentistry. These courses were chosen because they have the largest number of students and, consequently, dropouts in the institution. It is, therefore, an investigation into the scenario of retention in higher education, with a view to permanence management and strategies to retain students. The sources of this research are: Reference for the University of Burgos Project (Spain), the Unit Mentorship Project, the Unit's educational statistics, among others. Regarding the theoretical options, this is a study based on the assumptions of affiliation, in Coulon's terms, using the concepts of tactics and strategy, according to Certeau. The methodology focused on quanti-qualitative and autobiographical research, in the terms of Delory-Momberger. In view of this, it is concluded that the Mentoring Project is an efficient strategy for welcoming new students, promoting the engagement between veteran students and freshmen at the Unit.